Changes of microbial load in packet orange juice after expiration date - Feroz, Farahnaaz (Stamford Journal of Microbiology, 2019)
Fruit juice is popular product in the markets worldwide, with a market potential of approximately 230 million liters. Fruit juice although nutritious and beneficial for health can also serve as a vehicle for foodborne diseases. Most commercially available products are labelled with a use by date. These are applicable at a consumer and food handler levels, instructing them on the amount of days after opening within which a product must be consumed. It is important to identify the changes that occur after expiration date to have a better understanding of when food spoilage occurs and how long foods may be preserved, in order to reduce food wastage. The current study attempted to identify the changes that occur in orange juice after the expiration date printed on the product packaging. One to seven days after expiration results showed very little change. Increase in the microbial load was observed after day 14, after which a steady increase was observed in total viable bacteria, fungus, E. coli, and Staphylococcus spp. No changes were observed in other examined organisms. Stamford Journal of Microbiology, Vol.8(1) 2018: 27-29